Patient death and nurses’ coping strategies: Perception of nurses at a tertiary referral hospital in Kenya - Peris Wategi Kiarie; Gabriel Okombo; Wambui Makobu; Joel Ambikile; Mary B. Adam (PLoS ONE, 2026)
In healthcare facilities, patient deaths are a common occurrence, exposing nurses to diverse behavioral and emotional reactions, particularly within the context of resource constraints in Kenyan healthcare settings. This study aimed to investigate the experiences of nurses at AIC Kijabe Hospital in Kenya regarding patient death and their coping strategies. The focus group discussions sought to understand factors influencing nurses’ reactions to death, assessing the adequacy of their basic training in preparing them for coping, exploring the determinants of their coping strategy choices, and gathering recommendations for enhancing coping mechanisms. Employing qualitative research, six focus group discussions were conducted with 50 nurses from various hospital departments, including the emergency department, medical and surgical wards, intensive care unit, and maternity ward. After data collection, the information was transcribed verbatim and analyzed using a thematic analysis approach with inductive coding. Two researchers independently coded the data. A code was an identifying term for a specific part with emphasis on the aspect being investigated. Subsequently, the research team met to compare the codes and reached a consensus on the best interpretation of the data codes. The coding was then categorized into themes and Subthemes. The study findings revealed four overarching themes: individual process, institutional process, work team relationships, and educational gaps. In the individual process, nurses disclosed factors influencing their reactions to and feelings about death, encompassing Stress injuries, views of life (pessimism or optimism), cultural background, religious beliefs, and self-drive/self-management. Nurses expressed immediate emotional responses to the word “death” and conveyed the emotional toll of losing patients. The institutional process delved into how the hospital assisted nurses in coping with patient deaths, revealing a lack of support or guidance in selecting coping mechanisms. Nurses advocated for psychological support, support groups, and counseling sessions. Work relationships and educational gaps were also featured, with nurses emphasizing the deficiency in training on the emotional and psychological aspects of coping with death. They advocated for enhancements in educational preparation to better equip nurses for the emotional challenges intrinsic to their profession.